2019
DOI: 10.1038/s41593-018-0311-1
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of function of NCOR1 and NCOR2 impairs memory through a novel GABAergic hypothalamus–CA3 projection

Abstract: Nuclear receptor corepressor 1 (NCOR1) and NCOR2 (also known as SMRT) regulate gene expression by activating histone deacetylase 3 through their Deacetylase Activation Domain (DAD). We show that mice with DAD knock-in mutations have memory deficits, reduced anxiety levels, and reduced social interactions. Mice with NCOR1/2 depletion specifically in GABAergic neurons (NS-V mice) recapitulated the memory deficits and had reduced GABRA2 expression in lateral hypothalamus GABAergic neurons (LH GABA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 80 publications
(101 reference statements)
6
93
0
Order By: Relevance
“…with strong links to psychiatric and neurodevelopmental disorders and synaptic function and neuronal excitability ( Fig. 5b) [62][63][64][65][66][67][68][69][70][71][72]. Of note, two different isoforms from Circadian Locomotor Output Cycles Kaput (Clock), a gene involved in circadian rhythms and linked to depression and BD [73][74][75], were found to be differently altered (one more than threefold reduced and one more than fourfold increased) by circHomer1a knockdown (Fig.…”
Section: In Vivo Ofc Circhomer1a Knockdown Impairs Ofcmediated Behavimentioning
confidence: 99%
“…with strong links to psychiatric and neurodevelopmental disorders and synaptic function and neuronal excitability ( Fig. 5b) [62][63][64][65][66][67][68][69][70][71][72]. Of note, two different isoforms from Circadian Locomotor Output Cycles Kaput (Clock), a gene involved in circadian rhythms and linked to depression and BD [73][74][75], were found to be differently altered (one more than threefold reduced and one more than fourfold increased) by circHomer1a knockdown (Fig.…”
Section: In Vivo Ofc Circhomer1a Knockdown Impairs Ofcmediated Behavimentioning
confidence: 99%
“…The hypothalamus, located on the inferior portion of the diencephalon, contains a cluster of nuclei and tracts, and functions as the central controller influencing many body functions including those of the autonomic and endocrine systems [11]. Metabolism, heart rate, digestion, blood pressure, body temperature, limbic response, as well as stress-related factors, respiration [8], cerebral function, including memory [28], are all influenced by the hypothalamus. Sensory neurons terminate in the hypothalamus and in response efferent fibers extend into the brainstem and the spinal cord, where they synapse with neurons for example of the autonomic nervous system [25].…”
Section: Introductionmentioning
confidence: 99%
“…The depletion of NCOR1/2 in GABAergic neurons with Vgat-Cre (NS-V mice) causes learning and memory deficits ( 70 ). The electrophysiological analysis identifies the hyperexcitability of GABAergic neurons in the lateral hypothalamus (LH) in NS-V mice.…”
Section: Genetic Mammalian Modelsmentioning
confidence: 99%
“…Ribosome profiling identified that GABA A receptor subunits are downregulated in the LH GABA neurons in NS-V mice. This hypothalamic excitatory/inhibitory (E/I) imbalance impairs synaptic plasticity in the hippocampus CA3 region through a monosynaptic LH GABA -to-CA3 neural projection, which accounts for the neurocognitive dysfunction in NS-V mice ( 70 ).…”
Section: Genetic Mammalian Modelsmentioning
confidence: 99%
See 1 more Smart Citation